The Development of Modified Snake and Ladder Game to Teach English Vocabulary for Seven Grade Students - Al Khamim, Muhammad Nur Ihza Risqya Ardy; Makrifah, Istina Atul; Mubarok, Tyas Alhim; Waluyo, Bagus (PROJECT (Professional Journal of English Education), 2026)
This study aimed to develop a revised version of the Snake and Ladder game as an educational tool to facilitate the acquisition of English vocabulary among seventh-grade students at MTs Hidayatullah Blitar by employing a Research and Development (R&D) methodology within the framework of ADDIE. The initial outcomes revealed that vocabulary instruction was predominantly teacher-centric and predominantly reliant on textbooks, culminating in diminished motivation and restricted vocabulary proficiency. To mitigate this predicament, an interactive and non-digital game-based medium was conceived and developed. The validation outcomes demonstrated that the instrument attained 90% validity (very valid), whereas both material and media validations reached 95% (very valid), indicating that the content, design, and technical components were suitable and well-structured. Moreover, student feedback revealed a percentage of 91.8%, classified as highly feasible, signifying that the game was captivating, enjoyable, and beneficial for vocabulary acquisition. Consequently, the revised Snake and Ladder game is regarded as a valid and feasible educational medium that augments students’ motivation and active engagement in the learning of English vocabulary.